Evaluating the Balance Between Privacy and Access in Digital Information Sharing. Issue 2 (22nd September 2021) - Beesley, Sarah J.; Powell, Alex; Groat, Danielle; Butler, Jorie; Hopkins, Ramona O.; Rozenblum, Ronen; Aboumatar, Hanan; Butler, Allison M.; Sugarman, Jeremy; Francis, Leslie; Brown, Samuel M.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Access to personal health records in an ICU by persons involved in the patient's care (referred to broadly as "family members" below) has the potential to increase engagement and reduce the negative psychologic sequelae of such hospitalizations. Currently, little is known about patient preferences for information sharing with a designated family member in the ICU. We sought to understand the information-sharing preferences of former ICU patients and their family members and to identify predictors of information-sharing preferences. DESIGN: We performed an internet survey that was developed by a broad, multidisciplinary team of stakeholders. Formal pilot testing of the survey was conducted prior to internet survey administration to study subjects. SETTING: Internet survey. Subjects: Subjects included English-speaking adults who had an ICU experience or a family member with ICU experience between 2013 and 2016. We used panel sampling to ensure an ethnically representative sample of the U.S. population. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: One thousand five hundred twenty surveys were submitted, and 1, 470 were included in analysis. The majority of respondents (93.6%) stated that they would want to share present and past medical history, either all or that related to their ICU stay, with a designated family member of their choosing. The majority (79%) would also want their designated family member to be able to access that information from a home computer. Although most respondents preferred to share all types of information, they indicated varying levels of willingness to share specific types of more sensitive information. Information-sharing preferences did not differ by age, sex, ethnicity, or type of prior experience in the ICU (i.e., patient or family member). CONCLUSIONS: In the context of an ICU admission, sharing personal health information with a person of the patient's choosing appears desirable for most patients and family members. Policies and implementation of regulations should take this into consideration.